Pengaruh Religiusitas dan Job Satisfaction terhadap Organizational Citizenship Behavior pada Anggota Brigadir di Polres Pamekasan - Hairil Susanto (Jurnal Litbang Polri, 2023)
The purpose of this study was to find out the role of religiousity and job satisfaction in predicting organizational citizenship behavior. This study involved 122 brigadier from police resort Pamekasan. The sample of this study chosen with random sampling technique. This study use quantitative method. Data were analyzed using ancova. The findings of the study revealed that religiousity has shared about 6,7 % and job satisfaction has shared about 7,1 % at predicting organizational citizenship behavior. This study showing that brigadier who already married had organizational citizenship behavior higher than brigadier who are not married yet, and the brigadier who have higher income more likely have more organizational citizenship behavior than the brigadier with a lower income. It was suggested for the next study to have more demographic comparison and another variabel that can give a contribute to organizational citizenship behavior.